Responding to crossover youth: a look beyond recidivism outcomes - Wright, Emily M. (Youth violence and juvenile justice, 2020)
Crossover youth are involved in both child welfare and juvenile justice systems. The Crossover Youth Practice Model (CYPM) promotes collaboration between these systems to inform decision making between the two agencies and better serve these youth. Yet, few outcome evaluations of the CYPM exist, especially those that assess outcomes beyond recidivism, such as case dispositions, case closure, or placement or living situations. This study examined whether the CYPM (n ¼ 210) decreased recidivism and increased system/case responses and positive outcomes among youth within 9–18 months after the youth’s initial arrest relative to a comparison group of crossover youth (n ¼ 425) who were arrested 1 year before the CYPM was implemented. Overall, the findings suggest that the CYPM in the jurisdiction under study dismisses or diverts crossover youth more often, closes delinquency cases more often, and leads to more home placements than was previously done in the jurisdiction, but it does not significantly reduce recidivism.